Nitrogen doped hierarchically porous carbon derived from glucosamine hydrochloride for CO2 adsorption. (October 2017) - Shi, Jinsong; Yan, Nanfu; Cui, Hongmin; Liu, Yuewei; Weng, Yaqing; Li, Dan; Ji, Xinyi
Graphical abstract: Highlights: Nitrogen doped hierarchically porous carbon is prepared from glucosamine. The carbon exhibits a high CO2 uptake of 4.5 mmol/g at ambient conditions. Nitrogen doping shows positive effects on CO2 uptake and adsorption selectivity. Abstract: Hydrothermal carbonization (HTC) of biomass is an attractive and sustainable method for the preparation of carbonaceous materials. In this work, nitrogen doped carbon with a hierarchically porous strucutre was successfully prepared through the HTC of glucosamine hydrochloride and the subsequent KOH activation. The resultant carbons were characterized with different techniques, and the effects of activation conditions on the porous structure were also discussed. The carbons showed outstanding CO2 adsorption properties, a high CO2 uptake of 4.5 mmol/g was achieved at 298 K and 1 bar. In order to analyze the influences of nitrogen doping, a pristine carbon sample with very close pore size distribution characteristics but higher porosity was also synthesized with glucose as the carbon precursor. The corresponding CO2 uptake at 298 K and 1 bar was 3.4 mmol/g. Our results revealed that the presence of ultramicropores was an essential prerequisite for CO2 adsorption at ambient conditions, while nitrogen doping showed positive effects on both CO2 uptake and the adsorption selectivity over N2 .